HAK DAN KEWAJIBAN JANDA CERAI MATI DALAM HUKUM ADAT LAMPUNG PEPADUN LAMPUNG TENGAH PERSPEKTIF GENDER - Qosim Khoiri Anwar; Habib Shulton Asnawi; Annikmah Farida (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2018)
This research examines the facts of injustice against the divorcee died in the customary law of Lampung Lampung Pepadun Marga Anak Represents the Middle Lampung. The fact of the injustice done to the women starting from the existence of a pattern of relations of power that lame between men with women. Justification authorities it can be born is backed by the social perception of perception in the form of the myths of superiority a man trusted by the community. This research method is the type of field research, which are sociological qualitative analysis method with ethnographic. The primary data source is the custom of Lampung Pepadun, religious figures, as well as widows divorcees to death. The purpose of this research is to know the rights and obligations of the divorcee died in the customary law of Lampung Lampung Pepadun Marga Anak Represents the Middle Lampung in the perspective of Gender. Research results themselves that the provisions of the law on the rights and obligations of the divorcee died in the customary law of Lampung Lampung Pepadun Marga Anak Represents the middle of conflicting and inconsistent with the principles of fairness and gender equality